2022
DOI: 10.56369/tsaes.3936
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital Networks (Scns) Reducing the Poverty on Cocoa Producing Households: Evidence From Osun and Ondo States of Southwestern Nigeria

Abstract: <p><strong>Background.</strong> Poverty is a state or condition in which a person or community lacks the capital required to meet their needs. Whereas, social capital has been described as a vital asset for poverty alleviation since it can provide access to that which is lacking; capital. This study suggests evidences that the poor farmers could benefit more from social capital. <strong>Objective.</strong> This study was conducted to assess the impact of social capital on poverty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Membership in agricultural organizations is a measure of social capital. It has been found to influence the social interaction and exchange of ideas among farmers (Bamire et al, 2002;Akinola et al, 2010;Akinola and Owombo, 2012;Kehinde and Ogundeji, 2022). The result revealed that up to two-thirds (63.7%) of the sampled farmers belong to one organization or another.…”
Section: Demographic and Socio-economic Characteristics Of The Respon...mentioning
confidence: 98%
“…Membership in agricultural organizations is a measure of social capital. It has been found to influence the social interaction and exchange of ideas among farmers (Bamire et al, 2002;Akinola et al, 2010;Akinola and Owombo, 2012;Kehinde and Ogundeji, 2022). The result revealed that up to two-thirds (63.7%) of the sampled farmers belong to one organization or another.…”
Section: Demographic and Socio-economic Characteristics Of The Respon...mentioning
confidence: 98%
“…The Sargan standard over-identification test for instrument validation was conducted in this regard. The satisfying condition is that the instrument's p-value must exceed significance values of 0.1, to be a valid instrument ( Cawley and Meyerhoefer, 2012 ; Howley et al, 2015 ; Cawley et al, 2018 ; Kehinde and Ogundeji, 2022b ). The over-identification test result for Sargan is shown in Table 7 , and access to trade credit information is reported to be a legitimate instrument because its p-value is more than the significance threshold of 0.1.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ninh and Kieu (2019) , access to information on trade credit, cooperative membership, access to extension services and social organisation membership influence farmers' access to trade credit and might not significantly influence the dependent variable in question (use of EU-approved pesticide). Furthermore, following Cawley and Meyerhoefer (2012) , Howley et al (2015) and Kehinde and Ogundeji (2022b) , the Sargan over-identification test was also conducted for the IV models. If the P-value is not significant, it means that the instrument is not correlated with the error term and therefore it is valid (Kehinde et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation